MINERALIZACIÓN DE ORO EN LA FRANJA AURÍFERA DE VERAGUAS, PANAMÁ - Nelson, Carlos E. (2011)
Gold mineralization in the Veraguas Gold Belt of Panama is hosted by calc-alkaline volcanicrocks of mid-Miocene age. The volcanic rocks range in composition from basalt to rhyolite and are intruded bycoeval exogenous plugs and domes. Pyroclastic aprons surround the domes and host the ore deposits. The Remance mine, a vein and vein stockwork, has produced gold intermittently for over a century. Santa Rosa, ashallow epithermal stockwork and disseminated deposit, went into production in 1995. Gold discoveries in theVeraguas Belt focus attention on the exploration potential of hot spring systems and dome fields throughout Central America.